Carrier frequency and incidence of alpha-mannosidosis: population database-based study—focus on the East Asian and Korean population - Park, Jong Eun; Lee, Taeheon; Ha, Kyeongsu; Cho, Eun Hye; Ki, Chang-Seok (Frontiers in Genetics, 2023)
Background: Alpha-mannosidosis caused by mutations in the MAN2B1 gene is a rare genetic disorder characterized by physical abnormalities and intellectual disabilities. The objective of this study was to analyze the carrier frequency and estimated incidence of alpha-mannosidosis in East Asian populations, as limited data exists on its incidence in this group.In this study, a total of 125,748 exomes from the gnomAD database was analyzed. Additionally, 5,305 data from the KOVA and 1,722 data from the KRGDB, both representing Korean populations, were included.The global carrier frequency of alpha-mannosidosis in gnomAD was 0.23%; the highest carrier frequency was observed in the Finnish at 0.49%, and East Asians had the second highest carrier frequency at 0.30%. Globally, the approximate incidence of alphamannosidosis was calculated at 1 in 784,535, l in 166,801 Europeans (Finnish), and l in 431,689 East Asians. By integrating the data from the 8,936 Koreans in gnomAD Korean, KOVA and KRGDB, the carrier frequency of alpha-mannosidosis in the Korean population was 0.04% and estimated incidence was 1 in 19,963,024.This study is the first to investigate the carrier frequencies of alphamannosidosis in East Asians and Koreans, including specific subpopulations, utilizing gnomAD and the Korean genomic database. The variant spectrum of MAN2B1 genes in East Asians showed significant differences compared to other ethnic groups. Our data provide valuable reference information for future investigations into alpha-mannosidosis, aiding in understanding the genetic diversity and specific variants associated with the condition in East Asian populations.